2021
DOI: 10.17278/ijesim.1004076
|View full text |Cite
|
Sign up to set email alerts
|

Project VLOGI (Video Lectures on Giving Instructions): Effects on Learners’ Performance in Probability and Statistics

Abstract: This quantitative study ascertained the benefits of project VLOGI as an intervention to the eighth-grade students in resolving the usual unattained learning competencies in Probability and Statistics, especially in the last quarter of the school year. The researcher utilized the trueexperimental research design using vlogs as an intervention to this study. There were two (2) randomly selected classes out of the six ( 6) heterogeneous classes in school as (1) the control group (prevailing method) and (2) the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Regardless of all the issues impacting their performance in school, teachers are still guided by DepEd Orders. However, despite all these DepEd Orders, some teachers in any discipline, notably mathematics teachers, continue to be blind and deaf, leaving some topics unachieved in the curriculum guide before the school year closes (Batilantes, 2021). These are the circumstances of public-school teachers who continue to be blind and deaf in addressing neglected learning competencies every school year because they are preoccupied with their obligations as teachers and parents at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of all the issues impacting their performance in school, teachers are still guided by DepEd Orders. However, despite all these DepEd Orders, some teachers in any discipline, notably mathematics teachers, continue to be blind and deaf, leaving some topics unachieved in the curriculum guide before the school year closes (Batilantes, 2021). These are the circumstances of public-school teachers who continue to be blind and deaf in addressing neglected learning competencies every school year because they are preoccupied with their obligations as teachers and parents at home.…”
Section: Introductionmentioning
confidence: 99%
“…This content was inc luded in the seventh grade through tenth-grade mathematics curriculum guide (DepEd Mathematics Curriculum Guide, 2016). Countries involved, such as Thailand, Singapore, Ukraine, Latvia, Lithuania, Turkey, Canada, Hong Kong, Spain, and the Philippines, include probability and statistics in the last quarter of their curriculum guide (Batilantes 2021). Since the Probability and Statistics content was taught in the latter quarter of the school year, the researcher had found that it always has a low level of competence in higher grades .…”
Section: Introductionmentioning
confidence: 99%
“…Online learning is carried out remotely through the internet and other supporting tools such as cell phones and computers (Putria et al, 2020). The use of online learning assisted by access from modern technology based on mobile and technology has great potential and contribution in the world, especially as a transition and challenge to the use of learning using changes in the industrial revolution 4.0 in developing countries, especially in Indonesia and some part of the world and Asia (Batilantes, 2021;Roysa & Hartani, 2020;Spitzer & Musslick, 2021).…”
Section: Introductionmentioning
confidence: 99%